RESEARCH BASED ON THE PRINCIPLES OF CREATING HAPPINESS AND CHANGES IN LEANING PROCESS - chaiyanich, Parinut; Pluempan, Ruangsin (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2020)
Participatory Action Research: PAR is a research that combines participatory research. with action research as well as qualitative research together to acquire new knowledge to solving problems in the community, the community research team and villagers take part in research at every stage by the principle of creating happiness from thinking, making decisions, participating in the investigation and benefiting together with the learning process of the community by people centered development and problem-learning process is therefore not strange that many people understand that why does the knowledge gained from PAR research seem to be infinite? because research models like this generate infinite knowledge and lead to relationships in the field. More importantly, the researchers also embraced the aesthetic or principle of creating happiness from the spiral that results from changes in leaning process